2021
DOI: 10.1186/s40168-021-01165-z
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbiota shapes gut physiology and regulates enteric neurons and glia

Abstract: Background The intestinal microbiota plays an important role in regulating gastrointestinal (GI) physiology in part through interactions with the enteric nervous system (ENS). Alterations in the gut microbiome frequently occur together with disturbances in enteric neural control in pathophysiological conditions. However, the mechanisms by which the microbiota regulates GI function and the structure of the ENS are incompletely understood. Using a mouse model of antibiotic (Abx)-induced bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
137
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(141 citation statements)
references
References 102 publications
1
137
0
3
Order By: Relevance
“…Limited in vivo neurogenic potential in the ENS has been observed only after injury 6 , 8 , 9 , 10 , 12 , 13 ( Table 1 ). Kulkarni et al 11 challenged this dogma, suggesting that almost 70% of myenteric neurons are replaced within 1 week under normal physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Limited in vivo neurogenic potential in the ENS has been observed only after injury 6 , 8 , 9 , 10 , 12 , 13 ( Table 1 ). Kulkarni et al 11 challenged this dogma, suggesting that almost 70% of myenteric neurons are replaced within 1 week under normal physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Belkind-Gerson et al 8 , 9 used EdU labelling to analyze the distal colon and found no evidence of neuronal replication in adult mice. Similarly, Vicentini et al 10 found no evidence of neuronal replication after EdU labelling. Kulkarni et al 11 observed ∼70% turnover rate of enteric neurons after 1 week and 88% turnover rate after 2 weeks using IdU and CldU labelling in the ileum.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Finally, interneurons link the activity of ascending and descending motor networks to allow the “little brain” of the gut to function autonomously ( Figure 3 ). 39 , 51 The enteric nervous system is also supported by local glial cells, which also respond to changes in gut microbiota signaling, 52 but we will focus on enteric neurons in this review.
Figure 3.
…”
Section: Function and Anatomy Of The Peripheral And Enteric Nervous S...mentioning
confidence: 99%